Infusing Tri Hita Karana on Teaching Indonesian Vocabularies for Business for International Students - GDA Wicaksana; Yeni Suprihatin; Mar'an, Desy Awal (English Language Education Study Program, 2024)
This study aims to analyze the implementation of Tri Hita Karana during teaching Indonesian language for business for international students in Institut Desain dan Bisnis Bali. This study is a qualitative study by collecting the data through observation checklist and interview guide. This study is highly valuable for the reference of promoting the Balinese culture through Indonesia language courses in International classes. The data was analyzed qualitatively by selecting and displaying the data in descriptive as well as drawing conclusion. The result shows that Tri Hita Karana is implemented through drilling technique to fossilize the knowledge to their brain. By implementing project, the lecturer internalizes habituation to the students of Tri Hita Karana.